The Perceived Effectiveness of AI HR Helpdesk in Selected Teaching and Non- teaching Employees at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to evaluate the perceived effectiveness of an AI HR helpdesk amongteaching and non-teaching employees at Bestlink College of the Philippines. The studyemployed a quantitative research design, with a survey questionnaire as the primary data-gathering tool. The questionnaire assessed the participants' perception of the AI HRhelpdesk's effectiveness in addressing their HR concerns, as well as their satisfaction withthe overall function. The results of the study suggest that both teaching and non-teachingemployees perceive the AI HR helpdesk as an effective means of addressing their HRconcerns. The participants reported high levels of effectiveness with the AI HR helpdesk'sHR support, Easy access information, Data Privacy, Ticketing System, Availability, andautomated repetitive tasks in providing HR-related information and assistance. However, thestudy also identifies some areas for improvement, such as the need for more human-likeinteractions with the AI HR helpdesk. The study's findings provide valuable insights fororganizations that are considering implementing AI HR helpdesk systems. The study'sresults can guide organizations in developing and implementing effective AI HR helpdesksystems that meet their employees' needs and preferences. Based on the overall findings,most of the 190 respondents agree to implement or to have AI HR. Helpdesk in BestlinkCollege of the Philippines
Keywords: Business Administration